Livros de Psicologia recomendados para a formação de professores na reforma educacional Francisco Campos - Mário Casassanta (1927) - Luã Augusto da Silva Lança (2017)
The second decade of the twentieth century has an interesting production of books focused on Education and teacher training. That was a time when Psychology will be identified as one of the main sciences capable of contributing to the improvement of educational knowledge.Thus, analyzing the indication of Psychology books for teacher training contributes to the understanding of the development processes of Education and Psychology as fields of scientific production. The objective of this research is to analyze the set of bibliographical references indicated in the educational reform known as the Francisco Campos-Mário Casasanta Reform in Minas Gerais in 1927, for the training of teachers in the discipline of Psychology of the second year of the course of Adaptation of the Normal School Of Belo Horizonte. Thus, we identified which were the bibliographical references of Psychologyindicated by the reform law for the formation of teachers in normal schools; Analyzing, through these references, which knowledge of Psychology was proposed for the training of teachers in Minas Gerais, understanding how the State of Minas Gerais adopted these references as an indispensable strategy for the training of teachers in the scope of the Reformation. Through a historiographical study we analyzed as documentary sources the text of decree / law nº 8225 of 1928 that guides the program of education of the normal course in the State of Minas Gerais, elaborated from the educational reform of 1927, text that indicatesthe list of books / bibliographical references to be adopted in the discipline of Psychology, from which we analyze its summary with the purpose of verifying that knowledge should be in force within the scope of the reform and present itself as an auxiliary to Education. And together, we analyze the Journal of Teaching in Minas Gerais, specifically texts that work on themes related to Psychology of the time; Verifying a conjunctural panorama of how this science became part of the daily life of the educational agents of Minas Gerais. We use as theoretical support for the analysis, the concepts of "strategy" of Michel de Certeau and of "thinking collective" and "style of thought" by Ludwik Fleck; Seeking to understand which were the groups involved in the process of selection of bibliographic references. Concluding, therefore, that the Minas Gerais Government, through the books and knowledge of Psychology, aimed at teacher training, develops a polítical strategy aimed at choosing apsychological orientation for education in the State; Affirming the knowledge of the Institute Jean-Jacques Rousseau through Helena Antipoff.